Assessing the economic impacts of air transport development through nighttime light data : a case study of BIMSTEC nations - Saud, Harish Singh; Bhatt, Ayushman; Kunnawee Kanitpong; Ampol Karoonsoontawong; AIT Scholarship (Pathum Thani, Thailand : Asian Institute of Technology, 2025)
The advancement of air transportation is vital for fostering economic development. The BIMSTEC (2Bay of Bengal Initiative for Multi-Sectoral Economic and Technical Cooperation3) region is a group of seven countries, with a united GDP of approximately $4.7 trillion in 2023, and according to the latest census, the region is home to 1.73 billion people. According to transport connectivity master plan 2022 of BIMSTEC, it handles around 350 daily flights in regional destinations. Despite this, air transport development in this region remains uneven, with only India, Sri Lanka, and Thailand hosting international hub airports including top busiest airports. This study investigates the relationship and impact of air transport system development in the region, specifically the relationship between air traffic movements of all operating airports and its economic development. In addition, it also assessed the impact of air transport infrastructure on regional economic activities by studying the intervention of new airports. Three methods are employed in this study for analysis of relationship and impacts of air transport development on regional economy. The Generalized Least Square (GLS) model have considered 236 operational airports according to the availability of air traffic movement data from six nations. This model has used maximum 24 years of annual panel data of air traffic movement factors. It has been found that, except passenger movement of Myanmar, the correlation of all the countries air traffic movement has a significantly positive association with nighttime light (NTL) intensity which is the dependent variable as a proxy of economic activities. Similarly, to estimate the causal effect of new airport development in 25 treatment cities with 26 newly opened airports, quasi experimental approaches are used. 1940 control cities from five BIMSTEC countries are considered for matching purposes with treatment cities using propensity score matching. After matching, the estimated results obtained from TWFE DiD for the treated cities and post-treatment have found to be positively significant when considering all urban areas. In addition, the results of ATT and ATE estimated after matching, it is found that the outcome variable NTL by considering 15 and 25 regions is significantly positive and ATT is greater than ATE which means treated regions have more localized impacts of new airport intervention. However, the other outcome variables are also positive but not significant.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering in Transportation Engineering
Thesis (M.Eng.) - Asian Institute of Technology, 2025
Keywords: Bay of Bengal Initiative for Multisectoral Techno-Economic Cooperation; Airlines -- Economic aspects -- Southeast Asia; Aeronautics, Commercial -- Southeast Asia